Safety Personnel’s Perceptions on the Significant Factors that Affect Construction Projects Safety Performance - Abas, Nor Haslinda; Yusuf, Nurhalimah; Rahmat, Muhamad Hanafi; Tong , Yean Ghing (International Journal of Integrated Engineering, 2021)
The Malaysian construction industry has been long categorized as one of the riskiest industries due to the high number of accidents that happened at construction sites. The poor safety performance in the construction industry has caused several drawbacks and failures in the aspects of project performance, cost, project completion time, and productivity. One of the reasons that led to this situation is due to the inadequate awareness of the project safety performance factors. Therefore, this study aims to investigate the significant factors affecting the safety performance of construction projects, based on the perceptions of safety personnel. Fifty-six (56) questionnaires were distributed among construction safety personnel who are working at construction sites in Kuala Lumpur through email and face-to-face methods. The percentage of the returned questionnaire was 100%. The questionnaire was analyzed using the Average Index (AI) analysis to attain the significant factors that affect the safety performance of construction projects. The findings revealed that among significant factors that affect safety performance on the construction project through project level and organization level were safety training, safety rules and safety induction, and performance monitoring. The outcomes of the study could assist relevant parties especially contractors to avoid accidents occur and have a systematic improvement on safety performance indicators at the construction project.